Luminescence of silicon nanoparticles from oxygen implanted silicon. (1st November 2018) - Chulapakorn, T.; Sychugov, I.; Ottosson, M.; Primetzhofer, D.; Moro, M.V.; Linnros, J.; Hallén, A.
Abstract: Oxygen with a kinetic energy of 20 keV is implanted in a silicon wafer (100) at different fluences, followed by post-implantation thermal annealing (PIA) performed at temperatures ranging from 1000 to 1200 °C, in order to form luminescent silicon nanoparticles (SiNPs) and also to reduce the damage induced by the implantation. As a result of this procedure, a surface SiOx layer (with 0 < x < 2) with embedded crystalline Si nanoparticles has been created. The samples yield similar luminescence in terms of peak wavelength, lifetime, and absorption as recorded from SiNPs obtained by the more conventional method of implanting silicon into silicon dioxide. The oxygen implantation profile is characterized by elastic recoil detection (ERD) technique to obtain the excess concentration of Si in a presumed SiO2 environment. The physical structure of the implanted Si wafer is examined by grazing incidence X-ray diffraction (GIXRD). Photoluminescence (PL) techniques, including PL spectroscopy, time-resolved PL (TRPL), and photoluminescence excitation (PLE) spectroscopy are carried out in order to identify the PL origin. The results show that luminescent SiNPs are formed in a Si sample implanted by oxygen with a fluence of 2 × 10 17 atoms cm −2 and PIA at 1000 °C. These SiNPs have a broad size range of 6–24 nm, as evaluated from the GIXRD result. Samples implanted at a lower fluence and/or annealed at higher temperature show only weak defect-related PL. With further optimization of the SiNP luminescence, the method may offer a simple route for integration of luminescent Si in mainstream semiconductor fabrication.